(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Cefixime is an oral third-generation cephalosporin antibiotic. It is used to treat gonorrhea, tonsillitis and pharyngitis. The chromatography of the present invention is used to determine Cefixime trihydrate and Ornidazole in bulk drugs and pharmaceutical dosage forms. Separation and quantification were achieved on ACEC 18, 5μm,150 x 4.6 mm i. d. column. The Cefixime trihydrate and Ornidazole were exposed to acidic, basic, oxidative, neutral, thermal, and photolytic stress conditions, and stress samples were analyzed. The linearity of the Cefixime trihydrate concentration in the range of 10 - 60 μg mL was good, the correlation coefficient was 0.998, the Ornidazole correlation coefficient was 0.998, 25 -150 μg mL, and the correlation coefficient was 0.997. The intraday precision and accuracy of both analytes were less than 2 RSD.